Assessing the effect of the experimental parameters in the evaluation of the essential work of fracture in high-strength thin sheets. (July 2022) - Tarhouni, I.; Frómeta, D.; Casellas, D.; Costa, J.; Maimí, P.
Abstract: The essential work of fracture methodology (EWF) has been successfully adopted to evaluate the fracture toughness of various metals and polymers. However, some aspects of the methodology are still far less understood, such as the influence of the experimental parameters on EWF measurement in thin metal sheets. In the present paper, the ligament range criterion of the EWF approach was revised for several advanced high-strength steels (AHSS). The validity of the upper and lower ligament length limits given by the ESIS protocol is redefined and rationalized according to the necking capability and the plasticity behaviour of the different AHSS grades. The work provides a new criterion to define the minimum ligament length to be tested, based on the minimum distance required by the crack to fully develop the necking capability of the material. The width constraint is too restrictive and has no effect on the deviation from linearity in the upper range. On the other hand, the maximum ligament length is proven to be controlled by the size of the plastic zone as proposed by the ESIS protocol. Highlights: The ligament limits of the essential work of fracture are redefined for high strength sheets. A new criterion, considering the transition distance, is proposed to define the minimum ligament length. The mechanical properties and the strain hardening capacity control the failure mechanism in high strength steels. The fracture mechanism has influence on the lower ligament bound of the essential work of fracture.